Law of Desire : temporary marriage in Shi'i Iran - Haeri, Shahla, (Contemporary issues in the Middle East.)
Revised edition includes new postscript "Invitation to 'proper sex' : revisiting temporary marriage Mut'a in Iran" (pages 213-238), focusing primarily on the political and religious elite's discourse on temporary marriage.